Viruses of bivalve shellfish - Renault, Tristan (Libbey-Eurotext, Montrouge, FRANCE, 2006)
Bivalve molluscs are filter feeders and as a consequence they may bioaccumulate in their tissues viruses that infect humans and higher vertebrates. However, there have also been described mortalities of bivalve molluscs associated with viruses belonging to different families. Mass mortalities of adult Portuguese oysters, Crassostrea angulata, among French livestocks (between 1967 et 1973) were associated with irido-like virus infections. Herpesviruses were reported in the eastem oyster, Pacific oyster and European flat oyster and lately in scallops and clams. Disseminated neoplasia, a proliferative cell disorder of the circulatory system of bivalves, although of uncertain aetiology, has been suggested to be caused by retroviral infections. Other viruses described in bivalves are interpreted as members of the Papovaviridae, Togaviridae, Reoviridae, Bimaviridae and Picomaviridae. However, the lack of bivalve cell lines renders difficult virus isolation from molluscs. Les mollusques bivalves sont des filtreurs et de ce fait ils peuvent accumuler dans leurs tissus des virus d'origine anthropique. Par ailleurs, des mortalités ont été rapportées chez les bivalves en association à la détection de virus apparentés à différentes familles. Ainsi, des mortalités massives de l'huître portugaise, Crassostrea angulata, ont été observées entre 1967 et 1973 en France et associées à la présence de virus interprétés comme appartenant à la famille des Iridoviridae. Par ailleurs, des virus de type herpès ont été détectés chez différentes espèces de bivalves marins lors d'épisodes de mortalité. Des néoplasies touchant les hémocytes, les cellules circulantes de l'hémolymphe, sont décrites chez les mollusques bivalves et sont encore aujourd'hui d'étiologie incertaine. Cependant, l'implication de rétrovirus a été suspectée. D'autres virus interprétés comme appartenant aux familles des Papovaviridae, Togaviridae, Reoviridae, Bimaviridae et Picomaviridae ont été décrits chez les coquillages. L'absence de lignées cellulaires de bivalves ...